A security-oriented corporate culture of an organisation in a pandemic: A case study of WSB in Wroc±aw - Robert Majkut; Radosław Rybczyński (The Central European Review of Economics and Management (CEREM), 2021)
Aim: The paper aims to illustrate the importance of organizational culture in supporting security in an organization, on the example of a non-public higher education institution in Poland during the first year of the COVID-19 pandemic. Organization. Design/ Research methods: The case study is presented in the context of theoretical reflections. the authors participated in the process of change during the pandemic, influencing the social norms shaping the culture of the organization for safety purposes in order to ensure the effective functioning of this entity under an epidemic risk. Findings: This article has cognitive value and contains a description of the implemented procedures determined, on the one hand, by the organizational culture and, on the other hand, causing significant changes in the organization. Contribution: Until recently, Management Science and Organization and Management Sociology did not deal with developing a security-oriented corporate culture of a particular entity in the context of the threat of an epidemic. The results may provide an example of good practice, and is the basis of future research on post-COVID security management.
Keywords: Z13; 330; Organizational culture; Security of the organization; Creating a culture for the security of the organization; Pandemic; COVID-19